Computational techniques for text summarization based on cognitive intelligence - Priya, V. (Professor of computer science and engineering); Umamaheswari, K. (Professor of information technology) (Boca Raton : CRC Press, 2023)
"The book is concerned with contemporary methodologies used for automatic text summarization. It proposes interesting approaches to solve well-known problems on text-summarization using computational intelligence (CI) techniques including cognitive approaches. A better understanding of the cognitive basis of the summarization task is still an open research issue, an extent of its use in text summarization is highlighted for further exploration. With the ever-growing text and people on research has little time to spare for extensive reading, where, summarized information helps for a better understanding of the context at a shorter time. This book helps students and researchers to automatically summarize the text documents in an efficient and effective way. The computational approaches and the research techniques presented guides to achieve text summarization at ease. The summarized text generated supports readers to learn the context or the domain at a quicker pace. The book is presented with reasonable amount of illustrations and examples convenient for the readers to understand and implement for their use. The book is not to make readers understand what text summarization is, but for people to perform text summarization using various approaches. This also describes measures that can help to evaluate, determine and explore the best possibilities for text summarization to analyse and use for any specific purpose. The illustration is based on social media and healthcare domain, which shows the possibilities to work with any domain for summarization. The new approach for text summarization based on cognitive intelligence is presented for further exploration in the field"--
Concepts of text summarization -- Large scale summarization using machine learning approach -- Sentiment analysis approach to text summarization -- Text summarization using parallel processing approach -- Optimization approaches for text summarization -- Performance evaluation of large-scale summarization systems -- Applications and future directions.
OCLC-licensed vendor bibliographic record.
Keywords: Automatic abstracting; Text processing (Computer science); Computational intelligence; COMPUTERS / Computer Engineering; COMPUTERS / Artificial Intelligence; TECHNOLOGY / Electronics / General